Entrepreneurial Orientation And Its Effect On The Success Of Small Businesses - Putra, Gamal Stia; David, Wahyudi (Politeknik Siber Cerdika Internasional, 2025)
Entrepreneurial orientation (EO) has been widely recognized as a crucial driver of business success, particularly for small enterprises operating in competitive markets. This study aims to address this gap by examining the impact of EO on small business success in Indonesia. This study investigates the effect of EO dimensions—innovativeness, proactiveness, and risk-taking—on the success of small businesses in Indonesia. Using a quantitative approach with survey data collected from 150 small business owners across various sectors, the study applies multiple regression analysis to assess the relationships. The results reveal that innovativeness and proactiveness have a significant positive effect on business success, while risk-taking shows a moderate influence. These findings underscore the importance for small business owners to adopt innovative practices and proactively capitalize on market opportunities while mitigating risk. This research contributes to the growing body of literature on entrepreneurship in emerging markets, offering practical insights for entrepreneurs and policymakers on fostering small business growth.